Impact Of Online Shopping On Retail Trading Of Garments: A Study Among The Retail Outlets In Fancy Bazaar Area Of Guwahati City. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Online shopping means shopping through internet. It is an electronic commerce facilitating consumers to purchase directly from sellers all over the world through internet using web browser. It means establishing a virtual store, which provides all types of goods to the consumer for 24x7 just by a click from  phone or desktop. Some of the leading online stores currently in India are Amazon, Flipkart, Snapdeal, Myntra etc. The present paper tries to highlight the impact of online shopping in retail trading of garments: A Study among the Retail Outlets on Fancy Bazaar area of Guwahati city and for analysis the researcher has conducted a primary study through a well framed questionnaire meant for retail traders of garments in the study area and the secondary sources includes journals ,books, websites etc.